THE The Analysis Of The Impact Of Return On Asset, Return On Equity, And Ratio Of Liquidity, On Overall Company Performance: Case Study In Banking Sector Listed Indonesia Stock Exchange - Huliselan, Meny (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study analyzes the impact of Return on Assets (ROA), Return on Equity (ROE), and Liquidity Ratio on the overall performance of banking companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with a correlation research design. Through purposive sampling technique, 10 companies listed on the IDX were obtained as research samples. Using multiple linear regression analysis, the results show that ROA and ROE have a significant positive effect on company performance, which emphasizes the important role of profitability in financial success. However, Liquidity Ratio does not significantly affect performance, indicating that short-term liquidity management alone is not the main determinant of banking sector performance. These findings provide valuable insights for investors, financial managers, and policy makers in formulating strategies to improve banking sector growth. Future research can explore additional financial and non-financial factors to develop a more comprehensive framework for assessing company performance.